Advantages, disadvantages and optimization of one‐stage and chromogenic factor activity assays in haemophilia A and B. (6th July 2018) - Adcock, D. M.; Strandberg, K.; Shima, M.; Marlar, R. A.
Abstract: Haemophilia A and B diagnosis and disease severity classification are determined on the basis of results from factor VIII (FVIII) and factor FIX (FIX) activity assays, respectively. These assays are also used for potency labelling, postinfusion monitoring of factor replacement products and testing for FVIII/FIX inhibitors. This review focuses on activated partial thromboplastin time (APTT)‐based one‐stage assays (OSAs) and two‐stage chromogenic substrate assays (CSAs). Currently, there is considerable inter‐laboratory variability in the results obtained using OSAs, which can be intensified in a reagent‐specific manner by the presence of the new modified recombinant factor replacement products that are entering the market. Furthermore, the use of CSAs, which tend to show less variability, especially with the new modified products, is recommended in a number of clinical scenarios. Clinical laboratories may, therefore, need to establish CSAs for routine use. In this review, we aim to improve understanding and help establish best practices by describing the methodology behind OSAs and CSAs and highlighting assay advantages and limitations. We argue that there can be value in offering both assay methodologies in clinical laboratories that contribute to the care of patients with haemophilia A or B. Educating both laboratory scientists and clinicians about the strengths and weaknesses of each type of assay will help to establish the necessary dialogue that is key to ensuring not only that the appropriate assays are used in the right clinical situations, but also that the results are interpreted correctly.